Pediatric robot-assisted kidney transplantation: An initial case report in China - Yangyang Wu; Huixia Zhou; Pin Li; Xun Sun; Lifei Ma; Yang Zhao; Yuandong Tao; Jianchun Cui; Xiaoguang Zhou; Tian Tao; Ran Zhuo; Hongshuai Jia; et al. (Intelligent Surgery, 2023)
Objective: In this study, we aim to investigate the safety and feasibility of robot-assisted kidney transplantation (RAKT) in children by reporting our initial experience. Methods: Using the Da Vinci robotic system, we performed a successful RAKT on a 12-year-old child who had been on hemodialysis for 27 months. Results: The total operative time for the RAKT procedure was 245 min. The vascular anastomosis took 41 min, while the ureterovesical anastomosis lasted 18 min. The estimated blood loss during the surgery was 100.0 ml. Following the removal of the arterial and venous clamp, the kidney was well perfused, and no perioperative complications were observed. Conclusion: This study presents the first pediatric RAKT in China, proving the safety and feasibility of the robot-assisted technique for children awaiting kidney transplantation.